(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: The combination of different drugs or carrier materials in one single dosage form as well as new approaches to release control are among the advantages that 3D printing via Fused Deposition Modelling (FDM) may offer. The aim of this work was to examine the printing tablets with immediate release properties, gastro-resistant coating and processing parameters suitable for thermolabile drugs. Materials and Methods: The pharmaceutical polymers polyvinylpyrrolidone K12, polyethylene glycol 6000, Kollidon® VA64, polyethylene glycol 20,000 and Poloxamer 407 were extruded into drug loaded filaments (self-constructed extruder and Three-Tec ZE HMI; 2.8 mm nozzle diameter), 3D printed to tablets (Multirap M420; 0.35 mm nozzle diameter) and examined regarding their release behavior. Additionally, differently designed coatings based on the acid-stable polymer cellulose acetate phthalate were added using a dual extrusion printing technique. Results and Discussion: Tablets with the chosen polymers were printable at temperatures below 100 °C and showed fast to moderate drug release. The drug release of tablets based on polyvinylpyrrolidone K12 or polyethylene glycol 6000 with a drug load of 10% (m/m) pantoprazole sodium, a thermolabile model drug, was completed within 10 min or 29 min, respectively. Varying the 3D printing process by reducing the infill rate to create porous tablets enabled an even faster release within 3 min for polyvinylpyrrolidone K12 tablets. The printed gastro-resistant coat had a thickness of 0.4-0.5 mm, which is multiple times thicker than conventional coats obtained by spray coating. However gastro-resistance was not achieved completely, although a protection function was observed. Conclusion: A wide range of release profiles is achievable depending on the choice of polymer and the used tablet design. Regarding the manufacturing time of 3D printed formulations, this technique does not compete with high?throughput manufacturing of tablets to-date but offers a new field of complex new designs or individualized medicines.